Public Opinion, Public Support, and Counter-Attitudinal Voting on the U.S. Supreme Court. (1st October 2016) - Bryan, Amanda C.; Kromphardt, Christopher D.
ABSTRACT: Key questions in American politics are whether and why the Supreme Court is responsive to public opinion. Past scholarship has suggested a strong relationship between changes in public opinion and the ideological direction of the Court's decisions. Here we focus on a slightly different question and examine why justices are willing to follow public opinion, even at the expense of their own ideological preferences. To this end we examine whether justices are willing to vote contrary to their preferences when those preferences are out of step with prevailing public opinion. We employ a novel issue-specific measure of public mood, and we find that justices follow public opinion to shore up broader institutional approval. But the constraint of public opinion is not static over time. Rather, justices are uniquely responsive to public opinion when public support for the Court is low or case salience is high.